Elasticidaes renda e desigualdade da pobreza dos estados no Nordeste: uma análise do período de 1981 A 2009 - Lima Filho, Geraldo Feitosa (2011)
The objective of this study is to estimate and analyze the income elasticity of poverty and inequality in the Brazilian Northeast. For this, we used the Headcount (Po), the proportion of indigents, the Gini Index and Average per capita Income for the period 1981 to 2009. Regarding the methodology used to measure the elasticity, we chose to econometric techniques for panel data, given that information was used for the nine Northeast states in that period. The results showed that policies to reduce income inequality in the Northeast impacts on poverty reduction, in addition, the reduction of inequality has more impact in the fall in poverty levels than just the growth in average income.